The miticidal activity of silver nanoparticles towards phytophagous and predatory mites of citrus: efficacy and selectivity - Abdel Ghan, Sherif B.; Al-Azzazy, Mahmoud (Emirates Journal of Food and Agriculture, 2022)
o beyond bioassays within laboratory or growth chambers. Few studies have investigated the miticidal activity of SNP, mostly against Tetranychus urticae Koch (Acari: Tetranychidae). Despite the promising preliminary results, field evaluation of miticidal activity towards both pest and non-target organisms are still lacking. SNP were chemically synthesized utilizing trisodium citrate in excess and then miticidal activity was tested against phytophagous and predatory mites in trifoliate orange (Citrus trifoliata L.). A commercial formulation of Bifenthrin was used as reference. In laboratory, SNP showed slightly higher miticidal activity, than bifenthrin with LC50 of 29.3, 43.9 and 27.4 mg/l in SNP and 43.3, 38.9 and 31.6 mg/l in bifenthrin with efficiency factor of 1.5, 0.9 and 1.2 for P. oleivora, E. orientalis and B. obovatus, respectively. In case of SNP, it showed lower toxicity than bifenthrin towards predatory mites with LC50 of 789.9 and 656.0 mg/l in SNP and 48.2 and 45.5 mg/l in bifenthrin for P. oleivora, E. orientalis, and B. obovatus, respectively, with safety factor of 14 to 16 times for A. swirskii and P. plumifer, respectively. While in the field, LC50 values of SNP were 25.4, 36.0 and 27.0 mg/l while bifenthrin values were 39.2, 39.9, 29.7 mg/l for P. oleivora, E. orientalis and B. obovatus, respectively. SNP showed highly selective toxicity (23 times at LC50) towards phytophagous than predatory mites (P= 0.0001), whereas bifenthrin showed no selectivity (P= 0.750). Moreover, residues of SNP provided a 14-days prolonged activity against infesting mites. Exhibiting high selectivity towards the phytophagous mites, residues of SNP slightly affected the predatory ones. SNP showed comparable efficacy to bifenthrin for control of moving stages of P. oleivora, E. orientalis and B. obovatus mites and surpassed bifenthrin in ovicidal activity and saving associated predatory mites. SNP may be utilized for control of P. oleivora, E. orientalis, and B. obovatus mites in orange.